2019
DOI: 10.1029/2019gl083283
|View full text |Cite
|
Sign up to set email alerts
|

Whistler Waves Driven by Field‐Aligned Streaming Electrons in the Near‐Earth Magnetotail Reconnection

Abstract: We analyze Magnetospheric Multiscale Mission observations of whistler waves and associated electron field‐aligned crescent distribution in the vicinity of the magnetotail near‐Earth X‐line. The whistler waves propagate outward from the X‐line in the neutral sheet. The associated field‐aligned streaming electrons exhibit a crescent‐like shape, with an inverse slope (df/d|v|||>0) at 1–5 keV. The parallel phase velocity of the waves is in the range (1–5 keV) of the inverse slope of the field‐aligned crescents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
(83 reference statements)
0
23
0
Order By: Relevance
“…Such electron distributions may correspond to a parallel temperature anisotropy ( T e ⊥ / T e ‖ < 1) in the observations. The electron field‐aligned beams/crescent are a natural product of magnetic reconnection (Burch et al., 2016b; Ren et al., 2019). MMS studies show that field‐aligned electron beams are a common energy source for whistler waves (S. Huang et al., 2020; Ren et al., 2019; Zhao et al., 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such electron distributions may correspond to a parallel temperature anisotropy ( T e ⊥ / T e ‖ < 1) in the observations. The electron field‐aligned beams/crescent are a natural product of magnetic reconnection (Burch et al., 2016b; Ren et al., 2019). MMS studies show that field‐aligned electron beams are a common energy source for whistler waves (S. Huang et al., 2020; Ren et al., 2019; Zhao et al., 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Near the separatrix region of magnetotail reconnection, whistler waves are expected to be driven by field‐aligned electron beams (Fujimoto, 2014; S. Y. Huang et al., 2016; Zhou et al., 2011). Analysis of Magnetospheric Multiscale (MMS) observations in magnetotail reconnection demonstrates that electron field‐aligned crescent beams drive whistler waves through Landau resonance (Ren et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the Earth's magnetosphere, whistler mode waves can be generated by electron temperature anisotropy ( T ⊥ > T ∥ ) (Kennel & Petschek , ; Li et al, ) or electron beams (Ren et al, ; Sauer & Sydora, ). In this study, the whistler mode waves are generated by electron populations streaming on one side along the magnetic field and such a mechanism resembles the whistler heat flux instability (WHFI) (Kuzichev et al, ; Tong, Vasko, Marc, et al, ) observed in the solar wind.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Such waves have oblique wave normal angles of ∼45 • , have large amplitude electric fields with polarization close to linear, i.e., E ⊥ and E || of similar amplitude (Wilder et al, 2017;Khotyaintsev et al, 2019). Solving a kinetic dispersion solver using the observed electron distributions suggests whistler generation by electron beams is viable for both magnetotail and magnetopause conditions (Khotyaintsev et al, 2019;Ren et al, 2019).…”
Section: Whistlersmentioning
confidence: 99%